(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
Study of the history of lexical structure of Ukrainian language is impossible without finding out the history of individual semantic groups. Analysis odorativov in creativity Kotlyarevskyi, Kvitki-Osnovyanenko, Shevchenko is vocabulary smell in the Ukrainian language of the first half of the 19th century.